2005
DOI: 10.1021/bc040241m
|View full text |Cite
|
Sign up to set email alerts
|

PEG−Doxorubicin Conjugates:  Influence of Polymer Structure on Drug Release, in Vitro Cytotoxicity, Biodistribution, and Antitumor Activity

Abstract: Polymer-drug conjugates (polymer therapeutics) are finding increasing use as novel anticancer agents. Here a series of poly(ethylene glycol) PEG-doxorubicin (Dox) conjugates were synthesized using polymers of linear or branched architecture (molecular weight 5000-20000 g/mol) and with different peptidyl linkers (GFLG, GLFG, GLG, GGRR, and RGLG). The resultant conjugates had a drug loading of 2.7-8.0 wt % Dox and contained <2.0% free drug (% total drug). All conjugates containing a GFLG linker showed approximat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
204
1
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 275 publications
(220 citation statements)
references
References 28 publications
13
204
1
2
Order By: Relevance
“…Polymeric conjugates with high molecular weights had a prolonged blood circulation and higher tumor accumulation than low molecular weight conjugate, which is consistent to the results obtained with conventional pharmacokinetic studies [28,29]. The conjugate with 28 KDa eliminated rapidly from both blood pool and major organs due to its small size and fast excretion through renal filtration and had a relatively low tumor accumulation with short duration time.…”
Section: Discussionsupporting
confidence: 88%
“…Polymeric conjugates with high molecular weights had a prolonged blood circulation and higher tumor accumulation than low molecular weight conjugate, which is consistent to the results obtained with conventional pharmacokinetic studies [28,29]. The conjugate with 28 KDa eliminated rapidly from both blood pool and major organs due to its small size and fast excretion through renal filtration and had a relatively low tumor accumulation with short duration time.…”
Section: Discussionsupporting
confidence: 88%
“…It has been reported that the physiological activity of α-factor pheromone is closely correlated with affinity for the phospholipid membrane. [36][37][38] Since the target of α-factor is a membrane-associated protein, Ste2p receptor, a certain type of hydrophobic moiety attached to α-factor could aid pheromone localization to the target cell membrane, as do many other hormone such as Ras protein, 29,36-38 thereby leading to increased probability of binding. However, integration of a pheromone into the cellular lipid bilayer depends on the type of modification applied.…”
Section: Discussionmentioning
confidence: 99%
“…In tumor treatment the micelles system has proven effective in regression of tumor size while minimizing damage to the healthy tissues [4] and is being actively investigated in conjunction with hyperthermia [5], ultrasound [6], specific enzyme-induced cleavable bonds [7][8][9], and specific ligands or antibodies [10][11][12][13] for active targeting purposes.…”
Section: Introductionmentioning
confidence: 99%